Analysis of stereotactic biopsies for nonpalpable BIRADS 4 breast lesions: Evaluation of predictors for malignancy - Akbulut, Serkan; Avsar, Gokhan; Deryol, Riza; Bayar, Sancar; Eroglu, Aydan (Annals of Medical Research, 2021)
Aim: This study aims to determine the malignancy rates of nonpalpable BIRADS 4 breast lesions excised by stereotactic biopsy, the re-excision rates of malignant lesions detected by stereotactic biopsy and to evaluate the factors affecting malignancy rates in these lesions. Materials and Methods: Medical records of female patients admitted to the surgical oncology outpatient clinic between 2012 and 2017 with nonpalpable (<1 cm) BIRADS 4 breast lesions (either detected by USG or mammography) and underwent stereotactic breast biopsy were assessed. Results: The mean age of a total of 208 patients with 235 lesions underwent image-guided breast biopsy was 49.0± 0.6. In 54% of lesions, localization was superior outer quadrant and 51.1% of lesions were at left breast. In 46% of cases, radiological abnormality causing suspicion of malignancy was nodular lesion and the most encountered pathological result was proliferative breast lesion without atypia (62.1%). The mean age of the malignancy detected group after stereotactic biopsy was higher than benign group (p=0.048). In 16.2% (38/235) of the lesions, malignancy was detected and none of malignant lesions had lymph node metastasis. ER, PR and HER-2 positivity were 88.2% (30/34), 86.7% (26/30), and 30% (6/20), respectively. The re-excision rates of the malignant lesions to ensure oncologically acceptable surgical margins were 23.7% (9/38). Conclusion: Although malignancy, re-excision, and lymph node metastasis rates of non-palpable breast lesions underwent stereotactic biopsy with malignancy suspicion are not too high, careful evaluation of these lesions with malignancy suspicion is suggested in order not to miss malignant cases.